Spiritual Leadership, Religiosity, and Change Management Effectiveness: A Study in Educational Organisations - Jahroni Jahroni; Sanaji Sanaji; Andre Dwijanto Witjaksono; Anang Kistyanto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aimed to understand the influence of spiritual leadership and religiosity indicators on the effectiveness of change management in educational organisations as well as how spiritual leadership and religiosity interact in facilitating change in educational organisations. Using a qualitative method with a literature review approach, the study identified themes and patterns from various relevant sources. The results show that spiritual leadership plays an important role in formulating a vision, building a positive culture and increasing the commitment of organisational members. Indicators of religiosity such as individual religious commitment, piety and religious behaviour also contribute to successful change management. The interaction between spiritual leadership and religiosity can facilitate change by creating an environment that supports learning, overcoming resistance, and enhancing the well-being of organisational members